TRANSBOUNDARY WATER DEVELOPMENT PROBLEMS BETWEEN TAJIKISTAN AND UZBEKISTAN CONCERNING THE AMU DARYA RIVER - Sandy Satya Suryananda (HI 16 UMY 017, 2016)
*17 Water is one of the primary sources for humanity to survive, and it becomes a daily consumes for people around the world. The amount of clean water however, is decreasing over the years, since there are currently more people who live in this world than before. The increase of population and climate change had created a phenomenon of water scarcity. The emerging of water scarcity phenomena had triggered so many conflicts, just like what happened in Central Asia when Tajikistan planned to established a new dam which called Rogun Dam Hydroelectric Project in the Vakhs River, one of the downstream rivers of Amu Darya that is located near of Uzbekistan. After Tajikistan announced about the project, Uzbekistan was opposing it and applied many policies which made the Rogun Dam project slower. This paper will analyze the reason behind Uzbekistan disagreement towards Tajikistan’s Rogun Dam Hydroelectric project with using environmental security concept and neo classical theory as tools in order to analyze the reason behind Uzbekistan’s disagreement. The first thing that this paper want to prove is that Uzbekistan disagreement was mostly because of the impact of Rogun Dam project to water amount which is flowing in the Amu Darya river. Second, the decreasing amount of water in Amu Darya River will threaten Uzbekistan cotton industry and